FINANCIAL DEVELOPMENT AND POVERTY ALLEVIATION: A SYSTEMATIC REVIEW (Journal of Economics and Sustainability, 2024)
This study is conducted to validate the effectiveness of financial development in reducing poverty. The study adopted a Systematic Quantitative Assessment Technique and reviewed 91 financial development and poverty alleviation articles published between 2010–2022 to provide insight into the efficacy of financial development in reducing poverty and producing a blueprint for the government for possible adoption. The study also intends to know whether financial development successfully reduced poverty, highlight the evidence showing the success of financial development in reducing poverty, how financial development strategies were implemented to reduce poverty in other countries, and why financial development has been ineffective in reducing poverty. The reviewed articles revealed that financial development benefits the poor by increasing their access to various funding sources, thus improving well-being and reducing poverty. Similarly, it was revealed that lack of institutional quality and low financial penetration are the major reasons why financial development may not successfully reduce poverty. Thus, this study presented a FACI Blueprint to help the government effectively reduce poverty in countries where financial development is weak and unable to reduce poverty.